2013
DOI: 10.1002/bdrb.21053
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interleukin‐6 Signal Blockade on Immune System, Reproductive and Skeletal Development in Juvenile Mice

Abstract: Interleukin-6 (IL-6) is involved in the pathogenesis of multiple disorders, including juvenile autoimmune diseases. IL-6 participates in a broad spectrum of physiological events, and the IL-6 receptor (IL-6R) is widely distributed across multiple organs. The interrelationship of development phases in juveniles together with organs involved in IL-6 signaling called for evaluations of anti-IL-6R antibody induced effects in a juvenile mouse model to assess the safety of such an approach in human juvenile arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…All rat IgG and MR16-1-treated dKO mice were alive until 90 days of age, body weights were similar to non-treated dKO mice, and no abnormal morphologies were observed in the internal organs. A previous study also showed that there were no adverse effects of MR16-1 administration on sexual maturation or development of the immune and skeletal systems of juvenile wild-type [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All rat IgG and MR16-1-treated dKO mice were alive until 90 days of age, body weights were similar to non-treated dKO mice, and no abnormal morphologies were observed in the internal organs. A previous study also showed that there were no adverse effects of MR16-1 administration on sexual maturation or development of the immune and skeletal systems of juvenile wild-type [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the testis and placenta play different roles in prenatal regulation of steroidogenesis in humans and rodents ( Scott et al 2009 ), the present study supports the hypothesis that vascular disruption is a key event in MRDT, similar to pregnancy loss and other birth defects ( Abe et al 2013 ; Kleinstreuer et al 2011 ; Morita et al 2014 ). Several molecular targets were identified in the IL-6 pathway (CSNK2A1, MAPK3, IL6, JUN, STAT3, and FOS), but previous knockout studies failed to show that the IL-6 pathway was critical to rodent embryo development ( Sakurai et al 2012 , 2013 ; Yoshida et al 2011 ). In comparison, the finding of molecular targets in the MAPK pathway (MAPK3, IL1A, JUN, NFKB1, TGFB1, TNF, TP53, and FOS) is consistent with previous toxicity studies in Sertoli cells ( Qi et al 2014 ) and embryo limb bud cells ( Liu and Kapron 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous (IV) injection of a high dose of a soluble antigen was shown to induce a state of long-lasting, antigen-specific immune tolerance (high-dose immune tolerance) (13). This approach has been successfully used to enable a safety study with an immunogenic mAb in mice (14). However, high-dose immune tolerance induction is not applicable for studies in which low-single dose is used or necessary dose levels cannot be reached.…”
Section: Introductionmentioning
confidence: 99%